A species-wide genetic atlas of antimicrobial resistance in Clostridioides difficile. Issue 11 (18th November 2021) - Imwattana, Korakrit; Rodríguez, César; Riley, Thomas V.; Knight, Daniel R.
Abstract : Antimicrobial resistance (AMR) plays an important role in the pathogenesis and spread of Clostridioides difficile infection (CDI), the leading healthcare-related gastrointestinal infection in the world. An association between AMR and CDI outbreaks is well documented, however, data is limited to a few 'epidemic' strains in specific geographical regions. Here, through detailed analysis of 10 330 publicly-available C. difficile genomes from strains isolated worldwide (spanning 270 multilocus sequence types (STs) across all known evolutionary clades), this study provides the first species-wide snapshot of AMR genomic epidemiology in C. difficile . Of the 10 330 C . difficile genomes, 4532 (43.9 %) in 89 STs across clades 1–5 carried at least one genotypic AMR determinant, with 901 genomes (8.7 %) carrying AMR determinants for three or more antimicrobial classes (multidrug-resistant, MDR). No AMR genotype was identified in any strains belonging to the cryptic clades. C. difficile from Australia/New Zealand had the lowest AMR prevalence compared to strains from Asia, Europe and North America ( P <0.0001). Based on the phylogenetic clade, AMR prevalence was higher in clades 2 (84.3 %), 4 (81.5 %) and 5 (64.8 %) compared to other clades (collectively 26.9 %) ( P <0.0001). MDR prevalence was highest in clade 4 (61.6 %) which was over three times higher than in clade 2, the clade with the second-highest MDR prevalence (18.3 %). There was a strong association between specific AMR determinants and three major epidemic C. difficile STs: ST1 (clade 2) with fluoroquinolone resistance (mainly T82I substitution in GyrA) ( P <0.0001), ST11 (clade 5) with tetracycline resistance (various tet -family genes) ( P <0.0001) and ST37 (clade 4) with macrolide-lincosamide-streptogramin B (MLSB ) resistance (mainly ermB ) ( P <0.0001) and MDR ( P <0.0001). A novel and previously overlooked tetM -positive transposon designated Tn 6944 was identified, predominantly among clade 2 strains. This study provides a comprehensive review of AMR in the global C. difficile population which may aid in the early detection of drug-resistant C. difficile strains, and prevention of their dissemination worldwide.